Experiences, concerns, and needs of pregnant and postpartum women during the Covid-19 pandemic in Cyprus: a cross-sectional study - Hadjigeorgiou, Eleni; Vogazianos, Paris; Christofi, Maria Dolores; Motrico, Emma; Domínguez-Salas, Sara; Mesquita, Ana R; Christoforou, Andri (My University, 2022)
Background The current COVID-19 pandemic is a unique stressor with potentially challenging and negative consequences on the experiences of pregnant and postpartum women. International literature highlights the pandemic’s negative impact on women’s perinatal experiences. This is the first study in the scientific literature reporting on the impact of the COVID-19 pandemic, on the perinatal experiences of a large sample of women living in Cyprus. Aim To examine the impact of the COVID-19 pandemic on the experiences, concerns and needs of pregnant and postpartum women in Cyprus. Method The cross-sectional study was conducted from July 2020 to January 2021. A total of 695 women, 355 pregnant and 340 postpartum women (with infants up to 6 months of age), residing in Cyprus were surveyed. Results The great majority of the participants (80.9%) perceived the impact of the COVID-19 pandemic on their life as negative. The greatest sources of stress were identified and quantified for their impact on the participants. Our findings indicate that 74.1% of the pregnant women were concerned about changes due to COVID-19 measures impacting the presence of their family at the time of delivery, 57.2% about their newborn’s health, and 43.1% about changes related to perinatal care. Postpartum women’s concerns were mainly related to the welfare and health of their child (70.3%), whilst half of them (49.1%) expressed concerns about how they were going to care for their baby because of pandemic-related changes. Qualitative data revealed emerging themes as the basis of the pregnant and postpartum women’s concerns and needs. Conclusions The COVID-19 pandemic and the associated imposed measures and restrictions had adverse effects on pregnant and postpartum women’s perinatal experiences in Cyprus. The women’s concerns emphasized the need for the development of specialized, evidenced-based support systems which are essential particularly in pandemic-like situations, when pregnant and postpartum women are more vulnerable to isolation.
Keywords: COVID-19; Perinatal; Pregnant; Postpartum; Descriptive survey study